PLAN–DO–SEE: Lesson Study-Based Differentiated Learning in Middle Schools - Lestari, Andika Setyo Budi Lestari; Wahyono, Anton; Akkuşci, Yavuz Erdem; Purwanto, Purwanto; Anas, Khoirul; Nurmalasari, Yessi; Bibi, Rachma; Yunus, Mohamad (CV. Bimbimbingan Belajar Assyfa, 2023)
The Covid-19 pandemic hit almost all parts of the world, including Indonesia. It has been almost two years since the pandemic hit and has had an impact on various sectors including education. During the pandemic, learning was carried out online and felt less effective. Various government efforts have been made for faster recovery, especially in education. One of the government's efforts is through the KDS program (Lecturer-Teacher Partnership in Schools) through Lesson Study activities. This study aims to see the implementation of Lesson Study carried out together with junior high school teachers in partner schools. Through KDS (Lecturer-Teacher Partnership in School) activities by implementing Lesson study, compiling and implementing differentiated learning. The research method used is descriptive qualitative method. The subjects of this research were students of SMP. Lesson Study stages, namely planning (Plan), implementation (Do), reflection (See) which are carried out with lecturers as facilitators and teachers in partner schools as model teachers and observers have been carried out properly in accordance with Lesson Study guidelines and the learning objectives can be achieved planned. The results of research conducted through Lesson Study conducted with teachers in schools by implementing differentiated learning of student learning outcomes are mostly complete